Legal Politics as a Component for Improving the Minimum Service Standard for Early Childhood Education - Nurhasanah, Nia; Farma Rahayu, Mella Ismelina; Christiawan, Rio; Widyaningrum, Tuti (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2023)
Based on the Preamble to the 1945 Constitution of the Republic of Indonesia, the fourth paragraph refers to the ideals to be implemented within a single composition of the Republic of Indonesia. Article 28 C paragraph (1) of the 1945 Constitution of the Republic of Indonesia mandates that every person has the right to develop himself through meeting his basic needs, has the right to receive education and to benefit from science and technology, arts and culture, to improve for the quality of his life and for the welfare of humanity. This research aims to analyze legal politics in implementing the fulfillment of Minimum Service Standards (SPM) in Early Childhood Education (PAUD) in Indonesia. This research is normative legal research with a normative juridical approach. The research results show that the implementation of SPM in the PAUD sector is very important to ensure that every young child receives quality educational services. Article 11 of Government Regulation Number 2 of 2018 concerning Minimum Service Standards explains that local governments are obliged to implement SPM to fulfill the types of basic services and quality of basic services that every citizen has the right to receive. The implication is that the implementation of Minimum Service Standards (SPM) in Early Childhood Education (PAUD) is very important to ensure that every young child in Indonesia receives quality educational services, which ultimately contributes to improving the quality of life and human welfare.